Multi-Spectral and Fluorescence Imaging in Prevention of Overdose of Herbicides: The Case of Maize - Kouakou, Anicet K.; Soro, Adama P.; Taky, Alvarez K.; Zoueu, Jérémie T. (Scientific Research, 2017)
Evaluation of the impact of herbicides on maize was done through multispectral and multi-modal imaging and multi-spectral fluorescence imaging combined with statistical methods. Spectra containing 13 wavelengths ranging from 375 nm to 940 nm were derived from multi-spectral images in transmission, reflection and scattering mode and fluorescence images obtained using high-pass filters (F450 nm, F500 nm, F550 nm, F600 nm, F650 nm) on control maize samples and maize samples treated with Herbextra herbicide were used. The appearance of the spectra allowed us to characterize the effect of the herbicide on the maize pigment concentration. The fluorescence images allowed us to track the fate of absorbed energy and through PLS-DA and SVM-DA to discriminate the two leaf categories with very low error rates for the test, i.e. 4.9% and 2% respectively. The results of this technique can be used in the context of precision agriculture.
Keywords: Maize; Herbextra; Multi-Spectral Imaging; Multimodal Imaging; Fluorescence; PLS-DA; SVM-DA